THE EXISTENCE OF PANCASILA AS THE MILLENNIUM GENERATION’S PROTECTOR - Yori, Alifia (Jurnal Dinamika Sosial Budaya, 2022)
As the basis of the state whose substance has been considered absolute and has become a way of life for the Indonesian people, Pancasila has encountered various challenges in its practice. The millennial generation’s biggest challenge with their technological skills is influenced easily by things they do not understand. This article discusses how important the existence of Pancasila protect the nation’s next generation, or as we knew, the millennials, from the negative impacts of these technological advances and efforts to overcome them. This generation is a group of people burdened with bringing Indonesia forward with the knowledge they have. The development of technology has resulted in the existence and practice of values in Pancasila starting to fade. Purpose: This article aims to discuss the importance of the existence of Pancasila in the millennial generation to filter out some things that are considered incompatible with the character of the Indonesian nation from the Pancasila generation, as well as to find out what things should we do to restore the original character of the Indonesian nation. Methods: The method used is a literature review summary of 10 articles published in 2019, 2020, 2021. Conclusion: The results obtained through a study of 10 articles are that several factors support why Pancasila can protect the millennial generation and how to solve them.